What explains the spread of corporate social responsibility? The role of competitive pressure and institutional isomorphism in the diffusion of voluntary adoption - Han, Seungmin; Ito, Kiyohiko (Journal of Management & Organization, 2023)
This study provides a new perspective on the determinants of the spread of voluntary corporate social responsibility (CSR) adoption by incorporating the potential role of its adoption by industry competitors. We find supportive evidence that firms make CSR adoption decisions in response to competitive pressure as well as institutional mimetic pressures. Based on an event history analysis of longitudinal data from a sample of 711 Korean publicly traded firms over a 12-year period, our findings suggest that the CSR behavior of competitors is positively associated with a focal firm's earlier adoption of CSR, leading to the diffusion of CSR across firms. Specifically, this study shows that the pure rivalry-driven pressure from non-leader competitors has a stronger positive relationship with earlier CSR adoption. The results also indicate that a firm's CSR adoption decision is accelerated by competitive rivalry as well as social pressures arising from institutional mimetic isomorphism.
Keywords: Competitive strategy; corporate social responsibility; dept.mgt; institutional theory; peer-reviewed; quantitative methods

Environmental performance, environmental management and company valuation - Abrams, Roy; Han, Seungmin; Tanzeeb Hossain, Mehdi (Journal of Global Responsibility, 2021)
Purpose: This paper aims to investigate the relationship between environmental performance and management and company valuation. With a specific focus on company valuation, this study shows how a firm’s environmental activities, including its environmental management practices, are perceived and valued by its stockholders. Design/methodology/approach: Newsweek’s green ranking data between 2014 and 2016 were used to support this analysis. Environmental performances and environmental management practices of 345 Fortune 500 companies from various industries were included in the data set. Findings: The analysis finds higher valuations for US companies that are more efficient in managing greenhouse gas emissions. In addition, it empirically shows that investors place a higher value on companies with the following environment-related management policies: initiatives that reward top management for achieving environmental goals and third-party auditing of environmental performance. Originality/value: By incorporating corporate environmental management practices as an additional environmental performance criterion, this research fills a gap in the literature on the potential relationship between corporate environmental performance and company valuation. © 2021, Emerald Publishing Limited.
Keywords: dept.mgt; peer-reviewed

How Do Firms Build Green Supply Chain Learning System? A Theoretical Framework and Directions - Birasnav, M.; Han, Seungmin; Arora, Ridhi; Sangar, Ruby (Corporate Social Responsibility and Environmental Management, 2026)
Keywords: Green innovation; Mechanism (biology); Perspective (graphical); Resource (disambiguation); Supply chain; Supply chain management; Workforce; corporate social responsibility; dept.mgt; environmental performance; exploitation; exploration; green supply chain; leadership; learning system